Trace anodic migration of iridium and titanium ions and subsequent cathodic selectivity degradation in acid electrolysis systems. (December 2019) - Haraldsted, Jens-Peter B.; Révay, Zsolt; Frydendal, Rasmus; Verdaguer-Casadevall, Arnau; Rossmeisl, Jan; Kibsgaard, Jakob; Chorkendorff, Ib
Abstract: The oxygen evolution reaction in acidic electrolyzers requires the presence of stable catalysts and current collectors at the anode. IrO2 catalysts and Ti current collectors are among the best in this regard. We show evidence of iridium and titanium corrosion and subsequent membrane crossover in long-term experiments of proton-exchange membrane electrolyzers for H2 O2 production. The accumulation of trace iridium at the cathode was linked to degraded performance and increased cathodic current from hydrogen evolution. Detection of trace metal content at the cathode electrodes was enabled by prompt-gamma ray activation analysis and neutron activation analysis. These findings are not just relevant for H2 O2 electrolyzers but to any system using iridium-based anode catalysts, including CO2 electroreduction. Graphical abstract: Decentralized electrochemical devices using proton-exchange membranes (PEM) can sustainably synthesize industrial chemical commodities onsite via electrolysis. IrO2 catalysts are commonly used in PEM electrolyzers, and understanding the consequences of their inevitable corrosion is of critical importance to the advancement of these technologies. Specifically, the iridium ions migrating across the PEM and subsequently contaminating the working electrode is a fundamental degradation mechanism for the selective electrochemical production of chemicals other than H2 . Previous literature on degradation mechanisms in PEM devices is focused on H2 electrolyisis and H2 fuel cells, where this contamination would be irrelevant. We report the trace anodic metal crossover through the proton exchange membrane and the subsequent accumulation on the oxygen reduction reaction cathode in H2 O2 electrolyzers. The trace iridium contaminants were detected in electrode samples of varying degradation with neutron activation analysis and prompt gamma ray analysis (NAA/PGAA). The electrochemical activity of these iridium contaminants was determined by measuring the hydrogen evolution reaction. The trace electrochemically active iridium contaminants was linked to a loss in H2 O2 selectivity. This undesirable phenomena is applicable to similar systems that are selectively electrochemically producing chemicals, including CO2 electroreduction. Image 1